Consequential life cycle assessment of nature-based solutions for land restoration in Turin (Italy) and its first-belt municipalities - Martina Della Casa; Benedetto Rugani; Gabriele Guidolotti; Chiara Baldacchini; Carlo Calfapietra (Urban Forestry & Urban Greening, 2026)

Long-term monitoring of stem and root growth: Scale-dependent climatic regulation of radial increment in Canadian boreal forests - Negar Rezaie; Ettore D’Andrea; Roberto Silvestro; Annie Deslauriers; Carlo Calfapietra; Alessio Giovannelli; Sergio Rossi (Agricultural and Forest Meteorology, 2026)

Mitigating traffic-related particulate matter with evergreen shrubs: A real-world field study in bergamo, Italy - Maria Luisa Feo; Gregorio Sgrigna; Marco Torre; Francesca Marcovecchio; Chiara Anselmi; Dania Valli; Mattia Perilli; Simone Serrecchia; Giulio Esposito; Emanuela Tempesta; Francesca Trapasso; Ettore Guerriero; et al. (Environmental Pollution, 2026)

Carbon allocation traits are coordinated across plant organs, yet dry matter content is decoupled in three Mediterranean woody species - Gianluigi Ottaviani; Marta Magnani; Heath Beckett; Carlo Calfapietra; Mauro Lo Cascio; Mathieu Millan; Irene Tunno; Carlotta Volterrani; Silvia Portarena; Angelino Carta (Plant and Soil, 2026)
Background and aims Trait-based functional ecology often assumes that plant organs (e.g. leaf, stem, root) having dense tissues (high dry matter content; DMC) are carbon (C)-expensive. However, this assumption remains largely untested. Here, we examine whether 1) C-allocation traits co-vary forming coordinated functional strategies, 2) isotopic composition of leaf carbon (δ 13 C) can be effectively traced across organs and can estimate C present in upper soil layers thereby forming a plant-soil continuum, and 3) easy-to-collect traits can predict key soil ecosystem functions (C stock, nutrient status). Methods We focused on three widely distributed Mediterranean woody species ( Cistus salviifolius, Erica arborea , Quercus ilex ), measuring plant traits and soil parameters from three sites in Italy. We applied a Bayesian analytical framework considering the co-varying effects of biotic (species, developmental stage) and abiotic (site, fire disturbance) factors. Results Trait co-variation indicates integrated functional strategies for C allocation, especially for δ 13 C across organs. However, DMC of different organs is decoupled from %C and δ 13 C of the relative organ. We find no evidence for the occurrence of a δ 13 C plant-soil continuum, nor for easy-to-collect traits to predict soil functions. Conclusion The widely assumed positive relationship between DMC and C investment does not emerge in the three focal Mediterranean woody species, suggesting within-organ water content regulation as a key morpho-physiological adjustment in our model system. While the focal species are representative of the phylogenetic and functional variation in the Mediterranean woody flora, the generality of our findings should be tested in other regions hosting mediterranean-type ecosystems.

Soil Indicators for Evaluating Nutrient Cycling during Natural Regeneration in Postfire Forests Under Mediterranean Climate - Francesca Vannucchi; Francesca Bretzel; Eliana Lanfranca Tassi; Silvia Traversari; Irene Rosellini; Maurizio Sarti; Cristiana Sbrana; Alessio Giovannelli; Gabriele Guidolotti; Carlo Calfapietra; Andrea Scartazza (Journal of Soil Science and Plant Nutrition, 2026)

City-scale health benefits from experimental results at the tree canopy level: Insights from a nature-based solution case study - Martina Della Casa; Satoshi Hirabayashi; Benedetto Rugani; Gabriele Guidolotti; Paola Gullino; Federica Larcher; Carlo Calfapietra; Chiara Baldacchini (Urban Climate, 2025)

Drivers of vascular species diversity on floodplain poplar stands: An integrated approach for ecological and functional assessment - Anna Corli; Francesca Vannucchi; Silvia Traversari; Simone Orsenigo; Alessio Giovannelli; Pier Mario Chiarabaglio; Francesco Chianucci; Carlo Calfapietra; Andrea Scartazza; Marco Carlo Mascherpa; Maria Laura Traversi; Luca Cristaldi; et al. (Forest Ecology and Management, 2025)

Are trait responses of tree species across pyroregions indicative of fire-modulated plant functional strategies? - José Maria Costa-Saura; Gabriele Midolo; Carlo Ricotta; Mara Baudena; Carlo Calfapietra; Mario Elia; Paolo Fiorucci; Simone Mereu; Costantino Sirca; Donatella Spano; Gianna Vivaldo; Gianluigi Ottaviani (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Modelling the environmental implications of phytoremediation in urban settings: A review of the integration of life cycle assessment and ecosystem services approaches - Lidia Favaretto; Benedetto Rugani; Carlo Calfapietra; Massimo Labra; Werther Guidi Nissim (Urban Forestry & Urban Greening, 2025)

Impact of drought on cooling capacity and carbon sequestration in urban green area - Gabriele Guidolotti; Terenzio Zenone; Theodore Endreny; Rocco Pace; Marco Ciolfi; Michele Mattioni; Emanuele Pallozzi; Negar Rezaie; Teresa Bertolini; Chiara Corradi; Carlo Calfapietra (Urban Climate, 2025)

Monitoring ink disease epidemics in chestnut and cork oak forests in central Italy with remote sensing - Alessandro Sebastiani; Matteo Bertozzi; Andrea Vannini; Carmen Morales-Rodriguez; Carlo Calfapietra; Gaia Vaglio Laurin (Remote Sensing Applications: Society and Environment, 2024)

Coupled life cycle assessment and business modelling to estimate the sustainability of using regenerated soils in urban forestry as nature-based solutions - Benedetto Rugani; Bernd Pölling; Martina Della Casa; Gabriele Guidolotti; Chiara Baldacchini; Axel Timpe; Carlo Calfapietra (Urban Forestry & Urban Greening, 2024)

A lack of focus on data sharing, stakeholders, and economic benefits in current global green infrastructure planning - Tian Ruan; Jouni Paavola; Faith Ka Shun Chan; Yaoyang Xu; Chiara Baldacchini; Carlo Calfapietra (Journal of Environmental Management, 2024)

Temperature dependence of emission of volatile organic compounds (VOC) from litters collected in two Mediterranean ecosystems determined before the flaming phase of biomass burning - Negar Rezaie; Emanuele Pallozzi; Paolo Ciccioli; Carlo Calfapietra; Silvano Fares (Environmental Pollution, 2023)

Green infrastructure sustains the food-energy-water-habitat nexus - Tian Ruan; Yaoyang Xu; Laurence Jones; Wiebke J. Boeing; Carlo Calfapietra (Sustainable Cities and Society, 2023)

Nature-based solutions in post-industrial sites: Integrated evaluation of atmospheric pollution abatement and carbon uptake in a German city - Martina Ristorini; Gabriele Guidolotti; Gregorio Sgrigna; Mais Jafari; Dagmar Knappe; Vittorio Garfì; Chiara Baldacchini; Axel Timpe; Carlo Calfapietra (Urban Climate, 2023)

An ultra-spatially resolved method to quali-quantitative monitor particulate matter in urban environment - Chiara Baldacchini; Gregorio Sgrigna; Woody Clarke; Matthew Tallis; Carlo Calfapietra (Environmental Science and Pollution Research, 2019)

Comparing estimates of EMEP MSC-W and UFORE models in air pollutant reduction by urban trees - Gabriele Guidolotti; Michele Salviato; Carlo Calfapietra (Environmental Science and Pollution Research, 2016)

Isoprenoid emission in hygrophyte and xerophyte E uropean woody flora: ecological and evolutionary implications - Francesco Loreto; Francesca Bagnoli; Carlo Calfapietra; Donata Cafasso; Manuela De Lillis; Goffredo Filibeck; Silvia Fineschi; Gabriele Guidolotti; Gábor Sramkó; Jácint Tökölyi; Carlo Ricotta (Global Ecology and Biogeography, 2014)
Aim The relationship between isoprenoid emission and hygrophily was investigated in woody plants of the I talian flora, which is representative of E uropean diversity. Methods Volatile isoprenoids (isoprene and monoterpenes) were measured, or data collected from the literature, for 154 species native or endemic to the M editerranean. The E llenberg indicator value for moisture ( EIVM ) was used to describe plant hygrophily. Phylogenetic analysis was carried out at a broader taxonomic scale on 128 species, and then refined on strong isoprene emitters ( S alix and P opulus species) based on isoprene synthase gene sequences ( I sp S ). Results Isoprene emitters were significantly more common and isoprene emission was higher in hygrophilous EIVM classes, whereas monoterpene emitters were more widespread and monoterpene emission was higher in xeric classes. However, when controlling for phylogeny, isoprene emission was not associated with EIVM , possibly due to the large presence of Salicaceae among hygrophilous isoprene emitters. Moreover, the distribution of isoprene emitters among EIVM classes was not related to I sp S ‐based phylogenesis in P opulus and S alix , suggesting that the gene has not undergone evolution linked to ecological pressure. In contrast, the monoterpene emission pattern is independent of phylogeny, suggesting that the evolution of monoterpenes is associated with transitions to more xeric habitats. Main conclusions Our results reveal an interesting ecological pattern linking isoprenoids and water availability. We suggest that isoprene is a trait that: (1) evolved in plants adapted to high water availability; (2) is replaced by more effective protection mechanisms, e.g. more stable isoprenoids, in plants adapting to more xeric environments; and (3) being strongly constrained by phylogeny, persists in S alicaceae adapted to more xeric environments.

Carbon-based secondary metabolites and internal nitrogen pools in Populus nigra under Free Air CO2 Enrichment (FACE) and nitrogen fertilisation - Zhi-Bin Luo; Carlo Calfapietra; Giuseppe Scarascia-Mugnozza; Marion Liberloo; Andrea Polle (Plant and Soil, 2008)

Future atmospheric CO 2 leads to delayed autumnal senescence - GAIL TAYLOR; MATTHEW J. TALLIS; CHRISTIAN P. GIARDINA; KEVIN E. PERCY; FRANCO MIGLIETTA; POOJA S. GUPTA; BENIAMINO GIOLI; CARLO CALFAPIETRA; BIRGIT GIELEN; MARK E. KUBISKE; GIUSEPPE E. SCARASCIA‐MUGNOZZA; KATRE KETS; et al. (Global Change Biology, 2008)
Growing seasons are getting longer, a phenomenon partially explained by increasing global temperatures. Recent reports suggest that a strong correlation exists between warming and advances in spring phenology but that a weaker correlation is evident between warming and autumnal events implying that other factors may be influencing the timing of autumnal phenology. Using freely rooted, field‐grown Populus in two Free Air CO 2 Enrichment Experiments (AspenFACE and PopFACE), we present evidence from two continents and over 2 years that increasing atmospheric CO 2 acts directly to delay autumnal leaf coloration and leaf fall. In an atmosphere enriched in CO 2 (by ∼45% of the current atmospheric concentration to 550 ppm) the end of season decline in canopy normalized difference vegetation index (NDVI) – a commonly used global index for vegetation greenness – was significantly delayed, indicating a greener autumnal canopy, relative to that in ambient CO 2 . This was supported by a significant delay in the decline of autumnal canopy leaf area index in elevated as compared with ambient CO 2 , and a significantly smaller decline in end of season leaf chlorophyll content. Leaf level photosynthetic activity and carbon uptake in elevated CO 2 during the senescence period was also enhanced compared with ambient CO 2 . The findings reveal a direct effect of rising atmospheric CO 2 , independent of temperature in delaying autumnal senescence for Populus , an important deciduous forest tree with implications for forest productivity and adaptation to a future high CO 2 world.

Woody biomass production during the second rotation of a bio‐energy Populus plantation increases in a future high CO 2 world - MARION LIBERLOO; CARLO CALFAPIETRA; MARTIN LUKAC; DOUGLAS GODBOLD; ZHI‐BIN LUO; ANDREA POLLE; MARCEL R. HOOSBEEK; OLEVI KULL; MICHAL MAREK; CHRISTINE RAINES; MAURO RUBINO; GAIL TAYLOR; et al. (Global Change Biology, 2006)
The quickly rising atmospheric carbon dioxide (CO 2 )‐levels, justify the need to explore all carbon (C) sequestration possibilities that might mitigate the current CO 2 increase. Here, we report the likely impact of future increases in atmospheric CO 2 on woody biomass production of three poplar species ( Populus alba L. clone 2AS‐11, Populus nigra L. clone Jean Pourtet and Populus × euramericana clone I‐214). Trees were growing in a high‐density coppice plantation during the second rotation (i.e., regrowth after coppice; 2002–2004; POPFACE/EUROFACE). Six plots were studied, half of which were continuously fumigated with CO 2 (FACE; free air carbon dioxide enrichment of 550 ppm). Half of each plot was fertilized to study the interaction between CO 2 and nutrient fertilization. At the end of the second rotation, selective above‐ and belowground harvests were performed to estimate the productivity of this bio‐energy plantation. Fertilization did not affect growth of the poplar trees, which was likely because of the high rates of fertilization during the previous agricultural land use. In contrast, elevated CO 2 enhanced biomass production by up to 29%, and this stimulation did not differ between above‐ and belowground parts. The increased initial stump size resulting from elevated CO 2 during the first rotation (1999–2001) could not solely explain the observed final biomass increase. The larger leaf area index after canopy closure and the absence of any major photosynthetic acclimation after 6 years of fumigation caused the sustained CO 2 ‐induced biomass increase after coppice. These results suggest that, under future CO 2 concentrations, managed poplar coppice systems may exhibit higher potential for C sequestration and, thus, help mitigate climate change when used as a source of C‐neutral energy.

Carbon partitioning to mobile and structural fractions in poplar wood under elevated CO 2 (EUROFACE) and N fertilization - ZHI‐BIN LUO; CARLO CALFAPIETRA; MARION LIBERLOO; GIUSEPPE SCARASCIA‐MUGNOZZA; ANDREA POLLE (Global Change Biology, 2006)
To determine whether globally increasing atmospheric carbon dioxide (CO 2 ) concentrations can affect carbon partitioning between nonstructural and structural carbon pools in agroforestry plantations, Populus nigra was grown in ambient air (about 370 μmol mol −1 CO 2 ) and in air with elevated CO 2 concentrations (about 550 μmol mol −1 CO 2 ) using free‐air CO 2 enrichment (FACE) technology. FACE was maintained for 5 years. After three growing seasons, the plantation was coppiced and one half of each experimental plot was fertilized with nitrogen. Carbon concentrations and stocks were measured in secondary sprouts in seasons of active growth and dormancy during 2 years after coppicing. Although FACE, N fertilization and season had significant tissue‐specific effects on carbon partitioning to the fractions of structural carbon, soluble sugars and starch as well as to residual soluble carbon, the overall magnitude of these shifts was small. The major effect of FACE and N fertilization was on cell wall biomass production, resulting in about 30% increased above ground stocks of both mobile and immobile carbon pools compared with fertilized trees under ambient CO 2 . Relative C partitioning between mobile and immobile C pools was not significantly affected by FACE or N fertilization. These data demonstrate high metabolic flexibility of P. nigra to maintain C‐homeostasis under changing environmental conditions and illustrate that nonstructural carbon compounds can be utilized more rapidly for structural growth under elevated atmospheric [CO 2 ] in fertilized agroforestry systems. Thus, structural biomass production on abandoned agricultural land may contribute to achieving the goals of the Kyoto protocol.

Gross primary production is stimulated for three Populus species grown under free‐air CO 2 enrichment from planting through canopy closure - Victoria E. Wittig; Carl J. Bernacchi; Xin‐Guang Zhu; Carlo Calfapietra; Reinhart Ceulemans; Paolo Deangelis; Birgit Gielen; Franco Miglietta; Patrick B. Morgan; Stephen P. Long (Global Change Biology, 2005)
How forests will respond to rising [CO 2 ] in the long term is uncertain, most studies having involved juvenile trees in chambers prior to canopy closure. Poplar free‐air CO 2 enrichment (Viterbo, Italy) is one of the first experiments to grow a forest from planting through canopy closure to coppice, entirely under open‐air conditions using free‐air CO 2 enrichment technology. Three Populus species: P . alba , P . nigra and P . x euramericana , were grown in three blocks, each containing one control and one treatment plot in which CO 2 was elevated to the expected 2050 concentration of 550 ppm. The objective of this study was to estimate gross primary production (GPP) from recorded leaf photosynthetic properties, leaf area index (LAI) and meteorological conditions over the complete 3‐year rotation cycle. From the meteorological conditions recorded at 30 min intervals and biweekly measurements of LAI, the microclimate of leaves within the plots was estimated with a radiation transfer and energy balance model. This information was in turn used as input into a canopy microclimate model to determine light and temperature of different leaf classes at 30 min intervals which in turn was used with the steady‐state biochemical model of leaf photosynthesis to compute CO 2 uptake by the different leaf classes. The parameters of these models were derived from measurements made at regular intervals throughout the coppice cycle. The photosynthetic rates for different leaf classes were summed to obtain canopy photosynthesis, i.e. GPP. The model was run for each species in each plot, so that differences in GPP between species and treatments could be tested statistically. Significant stimulation of GPP driven by elevated [CO 2 ] occurred in all 3 years, and was greatest in the first year (223–251%), but markedly lower in the second (19–24%) and third years (5–19%). Increase in GPP in elevated relative to control plots was highest for P. nigra in 1999 and for P. x euramericana in 2000 and 2001, although in 1999 P. alba had a higher GPP than P. x euramericana . Our analysis attributed the decline in stimulation to canopy closure and not photosynthetic acclimation. Over the 3‐year rotation cycle from planting to harvest, the cumulative GPP was 4500, 4960 and 4010 g C m −2 for P. alba , P. nigra and P. x euramericana , respectively, in current [CO 2 ] and 5260, 5800 and 5000 g C m −2 in the elevated [CO 2 ] treatments. The relative changes were consistent with independent measurements of net primary production, determined independently from biomass increments and turnover.

Influence of free air CO2 enrichment (EUROFACE) and nitrogen fertilisation on the anatomy of juvenile wood of three poplar species after coppicing - Zhi-Bin Luo; Rosemarie Langenfeld-Heyser; Carlo Calfapietra; Andrea Polle (Trees, 2005)

Production, turnover and mycorrhizal colonization of root systems of three Populus species grown under elevated CO 2 (POPFACE) - MARTIN LUKAC; CARLO CALFAPIETRA; DOUGLAS L. GODBOLD (Global Change Biology, 2003)
A fast growing high density Populus plantation located in central Italy was exposed to elevated carbon dioxide for a period of three years. An elevated CO 2 treatment (550 ppm), of 200 ppm over ambient (350 ppm) was provided using a FACE technique. Standing root biomass, fine root turnover and mycorrhizal colonization of the following Populus species was examined: Populus alba L., Populus nigra L., Populus x euramericana Dode (Guinier). Elevated CO 2 increased belowground allocation of biomass in all three species examined, standing root biomass increased by 47–76% as a result of FACE treatment. Similarly, fine root biomass present in the soil increased by 35–84%. The FACE treatment resulted in 55% faster fine root turnover in P. alba and a 27% increase in turnover of roots of P. nigra and P. x euramericana . P. alba and P. nigr a invested more root biomass into deeper soil horizon under elevated CO 2 . Response of the mycorrhizal community to elevated CO 2 was more varied, the rate of infection increased only in P. alba for both ectomycorrhizal (EM) and arbuscular mycorrhizas (AM). The roots of P. nigra showed greater infection only by AM and the colonization of the root system of P. x euramericana was not affected by FACE treatment. The results suggest that elevated atmospheric CO 2 conditions induce greater belowground biomass investment, which could lead to accumulation of assimilated C in the soil profile. This may have implications for C sequestration and must be taken into account when considering long‐term C storage in the soil.

Monoterpene emission and monoterpene synthase activities in the Mediterranean evergreen oak Quercus ilex L. grown at elevated CO 2 concentrations - Francesco Loreto; Robert J. Fischbach; Jörg‐Peter Schnitzler; Paolo Ciccioli; ENZO Brancaleoni; Carlo Calfapietra; Guenther Seufert (Global Change Biology, 2001)
Monoterpene emissions, monoterpene synthase activities, photosynthesis, fluorescence yield in the dark and drought stress indicators (stomatal conductance and mid‐day water potential) were concurrently measured under similar temperature and illumination in current‐year leaves of Quercus ilex L. of plants grown in open‐top chambers at ambient (350 ppm) and elevated (700 ppm) CO 2 . The study was undertaken to understand the effect of CO 2 on monoterpene biosynthesis, and to predict and parameterize the biogenic emissions at growing CO 2 concentrations. The results of the 1998 and 1999 studies show that at elevated CO 2 , and in the absence of persistent environmental stresses, photosynthesis was stimulated with respect to ambient CO 2 , but that the emission of the three most abundantly emitted monoterpenes (α‐pinene, sabinene and β‐pinene) was inhibited by approximately 68%. The enzyme activities of the monoterpene synthases catalysing the formation of the three monoterpenes were also inhibited at elevated CO 2 and an excellent relationship was found between monoterpene emission and activity of the corresponding enzyme both at ambient and elevated CO 2 . Interestingly, however, limonene emission was enhanced in conditions of elevated CO 2 as it was also the corresponding synthase. The ratio between enzyme activity and emission of the three main monoterpenes was high (above 20) at ambient CO 2 but it was below 10 at elevated CO 2 and, for limonene, on both treatments. Our results indicate that the overall emission of monoterpenes at elevated CO 2 will be inhibited because of a concurrent, strong down‐regulation of monoterpene synthase activities. When the enzyme activity does not change, as for limonene, the high photosynthetic carbon availability at elevated CO 2 conditions may even stimulate emission. The results of the 1997 study show that severe and persistent drought, as commonly occurs in the Mediterranean, may inhibit both photosynthesis and monoterpene (α‐pinene) emission, particularly at ambient CO 2 . Thus, emission is probably limited by photosynthetic carbon availability; the effect of elevated CO 2 per se is not apparent if drought, and perhaps other environmental stresses, are also present.